Nona the ninth - Muir, Tamsyn (Muir, Tamsyn. Locked tomb trilogy, 2022)
"Tamsyn Muir's New York Times and USA Today bestselling Locked Tomb Series continues with Nona ...the Ninth? "You will love Nona, and Nona loves you." -Alix E. Harrow "Unlike anything I've ever read." -V.E. Schwab on Gideon the Ninth "Deft, tense and atmospheric, compellingly immersive and wildly original." -The New York Times on Gideon the Ninth Her city is under siege. The zombies are coming back. And all Nona wants is a birthday party. In many ways, Nona is like other people. She lives with her family, has a job at her local school, and loves walks on the beach and meeting new dogs. But Nona's not like other people. Six months ago she woke up in a stranger's body, and she's afraid she might have to give it back. The whole city is falling to pieces. A monstrous blue sphere hangs on the horizon, ready to tear the planet apart. Blood of Eden forces have surrounded the last Cohort facility and wait for the Emperor Undying to come calling. Their leaders want Nona to be the weapon that will save them from the Nine Houses. Nona would prefer to live an ordinary life with the people she loves, with Pyrrha and Camilla and Palamedes, but she also knows that nothing lasts forever. And each night, Nona dreams of a woman with a skull-painted face.."--